Development of Three-Dimensional Mesoporous Biocarbon Materials for Energy-Related Applications - Sani, Suleiman (2023)
The massive fossil fuel combustion in the post-industrial era to meet the world’s energy consumption has caused an increase in CO2 concentration in the environment. The use of various renewable energy technologies such as wind, nuclear, and solar have demonstrated excellent potential to reduce the rate of CO2 emissions. However, these energy technologies with renewable energies are not rapid enough to mitigate the impact of CO2 on climate change due to the low utilization ratio and erratic electricity supply. Among the carbon capture technologies, mesoporous carbons as supports to prepare polyethyleneimine (PEI)-modified sorbents for CO2 capture have attracted considerable attention due to significant sources of raw materials, high pore volume, organized pore geometry, and high efficiency and selectivity for CO2. This project aims to utilize the second and third most abundant biomass (chitosan and lignin) as renewable carbon sources to prepare bio-carbon materials with regulatable bimodal 3-dimensional (3D) interconnected mesoporous structures and evaluate their performance for CO2 capture. Firstly, a series of ordered mesoporous carbons with large mesopore sizes ranging from 9.6 to 14.1 nm and pore volumes ranging from 0.50 to 1.80 cm3/g were synthesized using lignin as a renewable and sustainable polymeric precursor and spherical siliceous mesostructured cellular foam (MCFs) as a template in a solvothermal process. The prepared lignin carbon materials showed a quasi-spherical porous morphology and were highly characterized by the rarely seen dominance of a three-dimensional large mesopore system that had a narrow pore size distribution centered at 20–25 nm with high surface areas of up to 960 m2/g and mesopore volumes of up to 1.50 cm3 /g. The results also showed that the large-pore mesoporous framework could be readily tuned by varying the carbonization/activation temperature and the silica-to-lignin ratio by mass. Secondly, ordered mesoporous carbon materials were synthesized using mesoporous silica SBA-15 as a template and lignin as a carbon precursor. The SBA-15-derived mesoporous carbons showed several exciting features: a 2-dimensional hexagonal structure, rod-like morphology, and a high surface area of up to 1076 m2/g with a moderate pore volume in the range of 0.29-0.66 cm3/g, and continuous evolution of average pore size from 3.87 to 4.01 nm. Thirdly, nitrogen-rich mesoporous materials were prepared in a solvothermal approach using biocompatible chitosan as both carbon and nitrogen sources and spherical siliceous mesostructured cellular foam (MCFs) as the templates. The pore structure, morphology, and chemical composition of the obtained materials were thoroughly characterized using nitrogen adsorption-desorption isotherms, scanning electron microscopy, transmission electron microscopy, and CHN elemental analysis. The results showed that the as-prepared mesoporous carbons had a high surface area in the range of 312-983 m2/g, large pore volume in the range of 0.22-1.32 cm3/g, a bimodal distribution of mesopore sizes in the range of 5-6.3 and 9-21.6 nm, and high nitrogen content of up to 10.48 wt%. Finally, amine-impregnated mesoporous carbon sorbents have been considered one of the most promising sorbents for CO2 capture from streams with low CO2 concentrations. A series of novel solid amine adsorbents were prepared by impregnating polyethyleneimine (PEI) on mesoporous carbons prepared using low-cost bio-waste material “lignin” as a carbon precursor via a facile templating method. The results demonstrated that the mesoporous carbon with 3D interconnected porous structure and large pore size and pore volume exhibited excellent CO2 adsorption capture of 2.90-3.13 mmol/g at a temperature operating window of 75-90 °C under CO2 partial pressure of 0.15 bar, being significantly higher than PEI impregnated sorbents prepared by using mesoporous carbon with 2D porous structures and also one of the best amongst other amine-impregnated adsorbents reported in the literature. The well-developed 3D interconnected mesoporous structure, high pore volume (up to 1.80 cm3/g), and large pore size permit the facile dispersion and immobilization of PEI within their pores and high availability of amine groups, which influences the high adsorption performance. In addition, the extended adsorption-desorption tests showed that the CO2 adsorbed by the PEI-impregnated adsorbent could be easily regenerated at 110 °C. It exhibited excellent cycling stability. Thus, these results indicate that the PEI-impregnated mesoporous adsorbents are ideal candidates for post-combustion CO2 capture.